2007
DOI: 10.1021/jf071736j
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Antioxidant Capacity during Storage of Selected Fruits and Vegetables

Abstract: Interest in the consumption of fresh fruits and vegetables is, to a large extent, due to its content of bioactive nutrients and their importance as dietary antioxidants. Among all of the selected fruits and vegetables, strawberries and black grapes have relatively high antioxidant capacities associated with high contents of total phenolic compounds, ascorbic acid, and flavonols. More interesting, the results of this study indicated that in most fruits and vegetables storage did not affect negatively the antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

59
174
7
15

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(255 citation statements)
references
References 45 publications
59
174
7
15
Order By: Relevance
“…3). These results are in agreement with those reported by Kevers et al 37 for red, yellow and green peppers (296, 284 and 215 mg/100g, respectively). The Yellow pepper presented a total polyphenol content of 329 mg GAE/100 g FW for ethanolic extract.…”
Section: Total Phenolssupporting
confidence: 94%
“…3). These results are in agreement with those reported by Kevers et al 37 for red, yellow and green peppers (296, 284 and 215 mg/100g, respectively). The Yellow pepper presented a total polyphenol content of 329 mg GAE/100 g FW for ethanolic extract.…”
Section: Total Phenolssupporting
confidence: 94%
“…This behavior has been previously reported in the literature. The flavonoid content of fruits increased or kept unchanged during ripening or storage, but during senescence, most flavonoids decreased (KEVERS et al, 2007).…”
Section: Total Flavonoids (Tf)mentioning
confidence: 96%
“…However, it is important to consider that AE depends not only on carotenoids, but also on other bioactive compounds present in the fruit. Kevers et al (2007) reported a relationship between the antiradical efficiency and the phenolic content in different fruits, so it is possible that these compounds and carotenoids have a significant influence on the AE in fruits treated at 15 MPa.…”
Section: Total Flavonoids (Tf)mentioning
confidence: 99%
“…Harvest time is essential to get a high quality fruit with storage potential. Some physiological properties can be affected by cultivar; agronomic condition and maturity stage [8]. Harvest date has also influence on fruit sensorial quality.…”
Section: Introductionmentioning
confidence: 99%